PENDAMPINGAN KEGIATAN PEMBELAJARAN SISWA DENGAN MEMANFAATKAN BARANG BEKAS UNTUK MENINGKATKAN MINAT DAN KREATIVITAS BELAJAR PADA MASA PANDEMI COVID-19 - Riza Faishol; Meliantina Meliantina; Eka Ramiati; Ellyana Ilsan Eka Putri; Syu’adah Murni Rahayu (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
Student learning assistance by utilizing secondhand goods aims to increase students' interest and creativity. This community service activity is carried out in several stages including: the preparation stage consisting of observation, interview to parents, delivery of strategies, and material bribery; the implementation stage consisting of socialization of the implementation of activities begins with the approach and mentoring of students; evaluation stage of the assessment of activities that have been carried out. The results of the activities that have been achieved are student learning assistance in preventing the transmission of corona virus, utilizing secondhand goods as a place to wash hands, utilization of used goods as handicrafts, and mentoring students in utilizing secondhand goods as a learning medium.